Enhanced Anticancer Efficacy of Dual Drug-Loaded Self-Assembled Nanostructured Lipid Carriers Mediated by pH-Responsive Folic Acid and Human-Derived Cell Penetrating Peptide dNP2 - Zhe Ma; Jiaxin Pi; Ying Zhang; Huan Qin; Bing Zhang; Nan Li; Zheng Li; Zhidong Liu (MDPI AG, 2021)
The poor ability of recognition and penetration of chemotherapeutic agents to tumor cells are still great challenges for targeted breast cancer treatment. Herein, we established a tumor-targeted nanostructured lipid carrier encapsulating gambogic acid (GA) and paclitaxel (PTX), which was co-modified with acid-cleavable folic acid (cFA) and a human-derived cell penetrating peptide dNP2 (CKIKKVKKKGRKKIKKVKKKGRK). The multi-functional nano-platform exhibited an enhanced targeting and penetrability to tumor tissues, which was accomplished by the combined action of cFA and dNP2. After intravenous injection, firstly, cFA could actively target the breast cancer tissues by the selective recognition of folate receptor (FR); then, upon arrival at the tumor microenvironment, the acid-cleavable FA and dNP2 dual modified nanostructured lipid carrier (cFA/dNP2-GA/PTX-NLC) exhibited sensitive cleavage of folic acid (FA), which could reduce the hindrance effect of FA to maximize the dNP2 cell-penetrating properties. The effect of different modification on cellular uptake, in vivo bio-distribution, and anticancer activity of NLCs proved our hypothesis that compared with NLCs modified by non-cleavable FA or a single ligand, cFA/dNP2-GA/PTX-NLC displayed more efficient intracellular delivery, stronger targeting ability in vivo, improved cytotoxicity on 4T1 cells, and produced the better therapeutic efficacy of GA and PTX. The strategy affords a feasible way to overcome the poor recognition and permeability of medicines in cancer treatment.